Prognostic Analysis of Primary Breast Signet Ring Cell Carcinoma and Mucinous Breast Adenocarcinoma: A SEER Population-Based Study - Wang, Song; Zhang, Yiyuan; Yin, Fangxu; Zhang, Xiangsheng; Yang, Zhenlin; Wang, Xiaohong (Frontiers in Oncology, 2021)
Background Primary breast signet ring cell carcinoma (SRCC) is a rare type of breast cancer with typical morphological characteristics, high aggressiveness, and poor prognosis. SRCC is different from mucinous breast adenocarcinoma (MBC). However, only a few studies have explored the clinicopathological features and prognosis of SRCC and MBC. Methods Data retrieved from the Surveillance, Epidemiology, and End-Results (SEER) database (2004–2015) were used to explore the prognostic effect of clinicopathological features and treatment modalities on survival outcomes of SRCC and MBC patients. Kaplan–Meier plot analysis, multivariate Cox proportional risk model, propensity score matching (PSM), and subgroup analysis were performed. Results A total of 167 patients with SRCC and 11,648 patients with MBC were included in the study. SRCC patients exhibited higher histological grade (p < 0.001), larger tumor volume (p < 0.001), higher rate of lymph node metastasis (p < 0.001), and higher frequency of distal metastasis (p < 0.001) compared with MBC patients. Cox proportional hazards regression analysis showed that SRCC patients had lower overall survival (OS) and breast cancer-specific survival (BCSS) compared with MBC patients. Subgroup survival analysis showed that the SRCC patients had lower OS and BCSS in subgroups including younger than 60 years old, white race, married, without chemotherapy, and received radiotherapy compared with the MBC patients in these subgroups. In addition, the SRCC patients had lower BCSS in subgroups including other races (including Asian or Pacific Islander and American Indian/Alaska Native), without surgery, and lymph node metastasis. Conclusion The findings showed that primary breast SRCC patients have unique clinical characteristics and worse prognosis compared with MBC patients. Notably, different treatment methods resulted in different prognosis for SRCC and MBC types; therefore, SRCC patients should be distinguished from MBC patients to improve efficacy of treatment.